The Implementation of the Qur'an Tahfidz Programme at SD Muhammadiyah MBS Prambanan, Sleman: A Case Study on Its Impact on Academic Character and Islamic Identity Development - Khoiru Ribath, Muhammad; Puji Astutik , Anita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Qur’anic education plays a pivotal role in shaping the moral and spiritual foundation of Muslim students. This study explores the implementation of the Tahfidz Al-Qur’an program at SD Muhammadiyah MBS Prambanan, focusing on its impact on students’ academic character development and Islamic identity. Employing a qualitative descriptive method, data were collected through interviews, observations, and documentation involving Tahfidz instructors, program coordinators, and sixth-grade students. Findings indicate that the program integrates structured memorization practices such as Talaqqi, Tahsin, Muroja’ah, and Tasmi’ within a pesantren-based curriculum. Key strategies include personalized mentoring, level-based memorization groupings, and formal assessments (munaqosyah) to evaluate students’ fluency and tajwid accuracy. Despite challenges such as heterogeneous memorization capabilities and limited instructional time, the program fosters discipline, spiritual resilience, and intrinsic motivation, supported by strong collaboration among teachers and parents. This study underscores the transformative role of Qur’anic memorization in nurturing both academic excellence and character integrity, offering implications for strengthening Qur’anic pedagogy in Islamic elementary education.